Cloning and sequence of GHRH gene of porcine hypothalamus - WANG Yi-zhen; YAN Xin-chun; YU Dong-you (浙江大学学报. 农业与生命科学版, 2000)
Porcine ds RNA was extracted from hypothalamus of finishing pig (Duroc × Yorkshire × Lan-drace). A pair or primers was designed according to the GHRH gene sequence reported previously. A cDNA fragment in length 132 bp was synthesized and amplified by RT-PCR. The PCR product was cloned into pGEM-T Easy vector and then sequenced. It was demonstrated that this fragment was GHRH gene cDNA. It has 132nts in length, which encodes a polypeptide containing 44 amino acids. Ho-mogenious analysis showed that it was consistent with the reported porcine GHRH gene sequence.